2017
DOI: 10.1002/fsn3.476
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and nutritional evaluation of a healthy vegetable soup powder supplemented with soy flour, mushroom, and moringa leaf

Abstract: The research study was conducted to develop a healthy vegetables soup powder supplemented with soy flour, mushroom, moringa leaf and compare its nutritional facts with locally available soup powders. Proximate analysis and sensory evaluation were done by standard method. In this study, moisture, ash, protein, fat, fiber, carbohydrate, and energy content were ranged from 2.83% to 5.46%, 9.39% to 16.48%, 6.92% to 16.05%, 4.22% to 6.39%, 0.22% to 1.61%, 58.81% to 75.41%, and 337.42 to 386.72 kcal/100 g, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 29 publications
5
52
5
3
Order By: Relevance
“…The higher ash content of our formulated instant drinks powder indicates that these are a better source of minerals. The ash contents of the instant mango drink powder were higher than reported by Akhter et al, (2010) for instant mango juice powder; Mohammed et al (2017) for instant sorrel (Zobo) drink and lower than reported by Farzana et al (2017) for vegetable soup powder and similar than reported by Obilana et al (2018) for instant beverage powder.…”
Section: Proximate Analysis Of Instant Mango Drink Powdercontrasting
confidence: 48%
“…The higher ash content of our formulated instant drinks powder indicates that these are a better source of minerals. The ash contents of the instant mango drink powder were higher than reported by Akhter et al, (2010) for instant mango juice powder; Mohammed et al (2017) for instant sorrel (Zobo) drink and lower than reported by Farzana et al (2017) for vegetable soup powder and similar than reported by Obilana et al (2018) for instant beverage powder.…”
Section: Proximate Analysis Of Instant Mango Drink Powdercontrasting
confidence: 48%
“…Similar results were obtained by Okafor et al [35], with replacement of wheat flour by mushroom powder, which resulted into increasing the protein content of the bread. Farzana et al [36] also observed an increase in vegetable soup powder supplemented with mushroom. Similarly, Ekunseitan et al [37] reported that adding mushroom flour to cassava and wheat flours increases the protein levels.…”
Section: Nutritional Quality Of Composite Floursmentioning
confidence: 90%
“…Other ingredients were collected from the local market. Soybean seeds, mushrooms, and moringa leaves were processed according to the procedure described previously (Farzana, Mohajan, Saha, Hossain, & Haque, 2017).…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…However, the locally available soup powders are not up to the mark in nutritional quality. The nutritional quality of traditional soup powders could be improved by supplementing it with mushroom, moringa leaf powders, and soy flour (Farzana & Mohajan, 2017;Wadud, Abid, Ara, Kosar, & Shah, 2004).…”
mentioning
confidence: 99%